Strong contrast in mass and energy balance between a coastal mountain glacier and the Greenland ice sheet - JAKOB ABERMANN; DIRK VAN AS; STEFAN WACKER; KIRSTY LANGLEY; HORST MACHGUTH; ROBERT SCHJØTT FAUSTO (Journal of Glaciology, 2019)
We show a strong difference in surface mass and energy balance of a mountain glacier and two sites on the ice sheet at 64°N in West Greenland using stake and automated weather station observations. Net surface mass balance is on average 2.2 m w.e. less negative at the coast compared with the ice sheet in the same elevation. We find a larger energy turnover at the ice sheet margin on Qamanarssup Sermia than measured on the coastal mountain glacier Qassigiannguit with both energy input and output being of larger absolute value. More cloudiness and a thicker snow cover at the relatively humid coastal glacier result in smaller gains in net-shortwave radiation and smaller losses in net-longwave radiation and a less negative mass balance. Lower wind speeds at the coastal glacier result in weaker turbulent heat exchange between atmosphere and ice surface. On annual average, 17 W m−2 more energy is available for melt at the ice-sheet margin compared with the coastal glacier in the same elevation.